(untitled) (Eurasian Medical Research Periodical, 2022)
Surgical treatment of conjugate non-accommodative and partialaccommodative strabismus gives positive cosmetic effect in the majority of operated eyes (from 50 to 100%) according to different authors. Wide variation in the value of positive effect is associated with heterogeneity of functional state of operated eyes, age of operation, and follow-up time. Several methods of strabismus surgery (recession/cutting, muscle duplication, and adjustable sutures to the muscle) are currently used